Effects of High Shearing Rates on the Shear Behavior of Saturated Loess Using Ring Shear Tests - Jianquan Ma; Xiaojie Zhao; Shibo Li; Zhao Duan (Geofluids)
The shear behavior of saturated loess was examined by performing a series of ring shear tests with different shearing rates. The effects of shearing rates on the shear behavior of saturated loess with different normal stress are presented and discussed. The results showed that peak shear strength and steady-state shear strength were greater when the shearing rate was low and vice versa. Compared with high and low shearing rates, the maximum strength reduction ratios of peak shear strength and steady-state shear strength were 34.2% and 37.2%, respectively. The axial displacement during shearing was measured and was found to increase with increasing shear displacement in all tests. A comparison of sample height reduction (when the shear rate was stopped) found that the low shearing rate test sample underwent a much greater reduction than the high shearing rate test sample; however, the variation reduction range was within 4 mm. Monitoring the pore-water pressure during the shearing process revealed that it increased with shear displacement, and a higher excess pore-water pressure was generated within the shear zone during the fast-shearing process. Comparing the particle size distribution of the samples after the test and the original sample showed that the particles were crushed during the shearing process. The percentage that was finer than 0.005 mm increased with shearing rates and normal stress, and the soil structure implosion became more pronounced with increasing normal stress.